2023
DOI: 10.3390/antibiotics12081316
|View full text |Cite
|
Sign up to set email alerts
|

Early Intra-Abdominal Bacterial Infections after Orthotopic Liver Transplantation: A Narrative Review for Clinicians

Abstract: Despite recent advances in the transplant field, infectious complications after orthotopic liver transplantation (OLT) are major causes of morbidity and mortality. Bacterial intra-abdominal infections (IAIs) are predominant during the first month post-transplantation and affect patient and graft survival. Recently, the emergence of multidrug resistant bacteria has generated great concern in OLT patients. We performed this narrative review of the literature in order to propose a “ready-to-use” flowchart for rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
(118 reference statements)
0
1
0
Order By: Relevance
“…The median [interquartile range (IQR)] age was 57 years (51-63 years), with a male preponderance (63.6%). The Median (IQR) Model for End-Stage Liver Disease was 17 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In seven cases (9.1%), DCD was implemented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median [interquartile range (IQR)] age was 57 years (51-63 years), with a male preponderance (63.6%). The Median (IQR) Model for End-Stage Liver Disease was 17 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In seven cases (9.1%), DCD was implemented.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that Gram-negative infections have a major role during the early post-OLT period, with pneumonia, bacteremia, and intrabdominal infections being the most frequent ones [1,[4][5][6][7][8][9][10][11]20,21]. In this scenario, beta-lactams are first-line treatments [12], and attaining an optimal PK/PD target early may allow for the maximization of clinical efficacy and suppress resistance development with beta-lactams [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Preexisting gut barrier dysfunction in patients with ESLD is further aggravated by the complex and long-time operational procedure and its associated I/R injury. Therefore, the bacterial translocation process is promoted during LT surgery and in the postoperative period, contributing to infectious complications [ 58 ]. In a prospective longitudinal study with LT patients, evaluating endotoxin concentrations in the perioperative period, patients with post-LT infectious complications had significantly higher endotoxin levels before LT and at the 14 postoperative day compared with those without complications [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…To this regard, it is noteworthy to highlight that in critically ill OLT recipients some specific features are most likely reported compared with general intensive care unit (ICU) patients. Specifically, intra-abdominal and/or biliary infections are prevalent among critically ill OLT recipients, and may account for up to 50% of early infections occurring after OLT (Van Delden, 2014;Taddei et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, hospitalacquired pneumonia (HAP), ventilator-associated pneumonia (VAP), bloodstream infections (BSIs), surgical site infections, and biliary/intra-abdominal infections are those most frequently reported (Weiss et al, 2010;Ikegami et al, 2012;Karapanagiotou et al, 2012;Patel and Huprikar, 2012;Van Delden, 2014;Antunes et al, 2015;Laici et al, 2018;Chueiri Neto et al, 2019;Massa et al, 2019;Wu et al, 2022). The prevalence of the different causative pathogens may greatly vary among the different transplant centers worldwide (Patel and Huprikar, 2012), but that of Gram-negatives is worryingly increasing nowadays (Patel and Huprikar, 2012;Giannella et al, 2023;Taddei et al, 2023). Unfortunately, most of these may be multidrug-resistant (MDR) or difficult-to-treat resistant (DTR) pathogens, and this pattern of resistance may affect clinical outcome, and cause prolonged antibiotic treatment (Patel and Huprikar, 2012).…”
Section: Introductionmentioning
confidence: 99%